The effectiveness of behavioral activation and antidepressant medication on the reduction of suicidality in patients with major depressive disorder - Latif Moradveisi; Marcus J.H. Huibers; Arnoud Arntz (BMC Psychiatry)
Abstract Antidepressant medication is commonly the preferred treatment for individuals with severe major depressive disorder (MDD). However, there is limited knowledge regarding how psychological therapy compares to medication in terms of its effects on suicidality. In a previous randomized clinical trial, we examined the effectiveness of behavioral activation (BA) against Sertraline for treating depression. The study included a total of 100 participants, with 50 assigned to the Behavioral Activation group and 50 to the Sertraline group. This paper focuses on the impact of both treatments on reducing suicidality in MDD patients. suicidality was measured using item 9 of the Beck Depression Inventory (BDI-II) and item 3 of the Hamilton Rating Scale for Depression (HRSD). Both treatments resulted in a decrease in suicidality; however, BA showed a greater reduction in scores on BDI-II item 9 and HRSD item 3 at 4 weeks, at the conclusion of the active treatment phase (week 13), and at the 49-week follow-up. At the 49-week follow-up, only 9% of patients in the BA group (4 out of 44) reported suicidal ideation, compared to 46.5% in the Sertraline group (20 out of 43) based on BDI-II item 9. Similarly, based on HRSD item 3, 9% of BA participants (4 out of 44) and 42% of Sertraline participants (18 out of 43) reported suicidality. Overall, BA was found to be more effective than Sertraline in reducing suicidality in both the short-term and long-term.